BSV710: Dissertation / College of Built Environment - UiTM, College of Built Environment (2018)
This course is to demonstrate a critical approach to Facilities Management problems and relate specific issues to developments in Facilities Management. The dissertation will also involve an investigation of the specific aspect of Facilities Management. The student will be required to plan, research, analyse, appraise and present the findings in report form. Each student is assigned a project supervisor who will assist them in establishing the research and objectives.